Perdebatan Ilmu Politik Sebagai Pengetahuan Ilmiah: Sebuah Tinjauan Ringkas - Ariesani Hermawanto (Jurnal Paradigma, 2013)
Political science as a branch of social science which had foundations, frame focus, and a clear scope; it can be said that political science is still young age because its birth in the late 19th century. As a scientific knowledge, political science has resulted debates among scientists. Because of these, the social science scholars have subsequently agreed with the definition of science is the sum of coordinated knowledge relative to determine subject). But many political scientist are not satisfied with this broad formulation, which then prompted experts to develop the scientific method. Political science need to use new ways to examines the symptoms and political events in a more systematic, relying empirical experiences using a detailed theoretical framework and rigorous. This new approach is known as behavioral approach. This behavioral approach encourages the development of political science as a scientific discipline until the present. Although this approach is not free from criticism, especially traditionalist approach, but in political analysis this approach is very useful to understand the political phenomenon.